2015
DOI: 10.1080/10408398.2014.965773
|View full text |Cite
|
Sign up to set email alerts
|

Alginate gel particles–A review of production techniques and physical properties

Abstract: The application of hydrocolloid gel particles is potentially useful in food, chemical, and pharmaceutical industries. Alginate gel particles are one of the more commonly used hydrocolloid gel particles due to them being biocompatible, nontoxic, biodegradable, cheap, and simple to produce. They are particularly valued for their application in encapsulation. Encapsulation in alginate gel particles confers protective benefits to cells, DNA, nutrients, and microbes. Slow release of flavors, minerals, and drugs can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
280
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 478 publications
(337 citation statements)
references
References 176 publications
2
280
0
11
Order By: Relevance
“…20,21 Notably, Lacy et al used alginate hydrogels (ALG) to encapsulate islet cells capable of releasing insulin. 22 3 Lab-scale synthesis of alginate hydrogel particles and fibers has been demonstrated using dripping, [23][24][25][26] co-extrusion, 27 microfluidics, 24,28,29 inkjet printing and 3D printing. 20,21 Bremond et al also demonstrated encapsulation with very thin controlled layers of alginate hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Notably, Lacy et al used alginate hydrogels (ALG) to encapsulate islet cells capable of releasing insulin. 22 3 Lab-scale synthesis of alginate hydrogel particles and fibers has been demonstrated using dripping, [23][24][25][26] co-extrusion, 27 microfluidics, 24,28,29 inkjet printing and 3D printing. 20,21 Bremond et al also demonstrated encapsulation with very thin controlled layers of alginate hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Rigid hydrogel beads can be formed by simple gelation with divalent cation with higher affinity to Ca 2+ and result in the egg-box formation. [20] Alginate has broad biological and food applications due to its biodegradability, biocompatibility, non-toxic and is reasonably cheap. [21,22] However, alginate hydrogels had poor mechanical properties and porous structure which are decisive for food or drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the immobilization of (O/W) single emulsions within Ca-alginate hydrogels through the crosslinking process could prevent the coalescence of oil globules and improve the stability of emulsions (Chan, 2011;Xiao, Shi, Li, Pan, & Huang, 2017). Alginate, an edible natural polysaccharide isolated from brown seaweed, is a linear polymer made up of α-1,4-l-guluronic acid residues and β-1,4-d-mannuronic acid residues (Ching, Bansal, & Bhandari, 2017). Alginate could rapidly form Ca-alginate hydrogel with calcium cations through a sol-gel transition, due to the formation of the well-known "egg-box" junctions (Aguero, Zaldivar-Silva, Pena, & Dias, 2017).…”
Section: Introductionmentioning
confidence: 99%